The last one home - Rimmer, Christine (Rimmer, Christine. Bravos of Valentine Bay., 2021)
"Ian McNeill has returned to Valentine Bay to meet the biological family he can't remember. Along for the ride is his longtime best friend, single mom Ella Haralson. Out of town in a new setting, Ian begins to see Ella in a more romantic light. But being separated from his family at a young age has left Ian wary of commitment. Will this unexpected reunion turn Ian into a family man in more ways than one?"--